Internal Acoustic Channel Diameter in Sudden Sensorineural Hearing Loss - Alpay, Hayrettin Cengiz; Yıldırım, Hanifi; Kaygusuz, İrfan; Karlıdag, Turgut; Keles, Erol; Orhan, İsrafil; Yalcın, Sinasi (Fırat University, 2013)
Objective: The purpose of our study was to determine the corelation between internal acoustic channel diameter and idiopathic sensorineural hearing loss. Material and Method: We defined sudden sensorineural hearing loss according to the criteria of Wilson as a 30-dB sensorineural hearing loss occurring in at least three contiguous frequencies in less than 3 days. The internal acoustic channel diameter all of the patients was measured from three dimensional temporal CT scan. Results: Of the 15 patients, 7 were male and 8 were female, ranging in age from 17 to 59 and the mean age was 39.6 years. The right ear was involved in 6 patients, and the left ear in 9. There was no statistically significant difference between the patients' affected and intact ears (p>0.05). However, the mean diameter of affected side of the patients was narrower than those of healthy controls (p

Amaç: İdyopatik ani işitme kaybıyla internal akustik kanal çapı arasındaki ilişkinin ortaya konulması. Gereç ve Yöntem: Wilson kriterlerine uygun olarak üç gün içerisinde oluşmuş, birbirini izleyen üç frekansta 30 dB işitme kaybı idiyopatik ani işitme kaybı olarak değerlendirildi. Hastaların internal akustik kanal çapları temporal bilgisayarlı tomografi yardımıyla internal akustik kanalın üç boyutlu görüntüsü elde edilerek ölçüldü. Bulgular: Çalışmaya alınan 15 hastanın yedisi erkek sekizi kadındı. Yaş aralığı 17 ile 59 arasında değişmekte olup ortalama yaş 39,6 idi. Onbeş hastanın altısında sağ, dokuzunda sol kulak tutulmuştu. Hastaların işitme kaybı olan kulaklarıyla sağlam kulaklarının karşılaştırılmasında istatistiksel olarak anlamlı farklılık yoktu (p>0.05). Ancak kontrol grubuyla karşılaştırıldığında etkilenen kulakta istatistiksel olarak anlamlı darlık tespit edildi (p
Ani İşitme Kaybında İnternal Akustik Kanal Çapı